Consumer responses to corporate social responsibility programs: The influence of company-cause fit and consumer involvement. Issue 4 (2nd November 2015) - Lu, Tim; Wei, Xia; Li, Kungchi
Abstract : Purpose: – The paper aims to establish a causal relationship model that helps to realize how consumer involvement with the cause moderates the effect of company-cause fit on consumers' corporate associations, and how their corporate associations regarding a company's social responsibility programs influence their satisfaction with the company and the company's corporate image, in the backdrop that the use of corporate social responsibility initiatives to affect consumers' preference has become a common strategy. Design/methodology/approach: – In the main study, the authors conducted a between-subjects factorial design to test the research model. A total of 400 questionnaires were distributed, and a valid sample of 389 participants was obtained. Findings: – The results show that high-fit programs have a positive influence on the perceived corporate ability (CA) and corporate social responsibility (CSR) associations. CA associations directly influence corporate image and consumer satisfaction, while CSR associations indirectly impact consumer satisfaction through corporate image. Furthermore, consumers' involvement with the cause increases the relationship between company-cause fit and CA associations. Originality/value: – These conclusions have important implications for a better understanding of consumer evaluation of CSR initiatives. Theoretically, this research increases understanding of the interaction effects of perceived company-cause fit and consumer involvement with the cause on consumer evaluation of a company engaged in CSR, and a richer insight into the role of CA and CSR associations in consumer evaluations of companies engaged in CSR campaigns. Managerially, this research shows how managers can choose CSR programs causes that are most likely to promote favorable customer CA and CSR associations, thereby improving the company's corporate image and customer satisfaction.